Monoclonal antibodies for the prevention of migraine. (2nd December 2019) - Raffaelli, Bianca; Neeb, Lars; Reuter, Uwe
ABSTRACT: Introduction : Calcitonin Gene-Related Peptide (CGRP) plays a crucial role in migraine pathophysiology. A novel specific treatment strategy for the prevention of migraine incorporates monoclonal antibodies (mAbs) against CGRP and its canonical receptor. Eptinezumab, fremanezumab and galcanezumab block CGRP mediated effects by binding to the peptide, while erenumab blocks the CGRP receptor. Areas covered : Following a brief overview of pharmacological characteristics, we will review phase III trials for the use of CGRP mAbs in the prevention of episodic and chronic migraine. Expert opinion : All four CGRP mAbs demonstrated an excellent safety, tolerability and efficacy profile in migraine patients. Across all trials mAbs showed superior efficacy for the reduction of monthly migraine days compared to placebo with a net benefit of 2.8 days. Neither cardiovascular nor immunological safety concerns have emerged from clinical trials. Fremanezumab, galcanezumab, and erenumab are approved in the USA and Europe. Based on trial data there is no reason why these mAbs should not become first-line therapies in future. For now, we advocate for the use of mAbs in migraine prevention for patients who failed a minimum of two standard oral treatments based on the novelty and costs of this approach. mAbs are also effective in patients with medication overuse and with comorbid depression or anxiety disorders. Taken together, mAbs are likely to usher in a new era in migraine prevention and provide significant value to patients.